A study of the medical causes of absence from duty aboard South African merchant ships. Issue 2 (April 1972) - Levy, Samuel
Abstract : Levy, S. (1972). Brit. J. industr. Med., 29, 196-200. A study of the medical causes of absence from duty aboard South African merchant ships. Over a period of four and a half years 556 instances occurred in which crew members were put off duty on medical grounds for a period of four or more days. Illness accounted for 297 cases whereas accidents were responsible for 259 cases. Illiness and accident cases were off duty for an average period of 28 and 34 days respectively. Slightly more working days were thus lost on account of accidents. Admission to hospital was required in 90% of illnesses compared with only 36% of accidents. Appendicitis (of questionable veracity), peptic ulceration, and psychiatric disturbances were among the more common causes of incapacity. Forty percent of accidents occurred on deck and in the cargo holds. Fractures occurred most commonly in the upper limbs, especially the hand. Eleven percent of the accidents occurred ashore, mostly due to assault. Further study is required to elucidate whether the emotional problems encountered are brought to sea by the personnel or are a result of life on board ship. The high incidence of accidents stresses the fact that a sea career is one of the more dangerous occupations.